Unsinkable - Long, Jessica Tatiana; Long, Hannah (Houghton Mifflin Harcourt, 2018)
Chronicles the life of Jessica Long and her journey to becoming one of the most decorated U.S. Paralympic swimmers in the world. Details her childhood, training, and her Olympic career, and highlights her life with her adoptive family and her relationship with her biological family in Russia. Includes color photographs.